2010
DOI: 10.1158/1940-6207.capr-09-0160
|View full text |Cite
|
Sign up to set email alerts
|

Meat Processing and Colon Carcinogenesis: Cooked, Nitrite-Treated, and Oxidized High-Heme Cured Meat Promotes Mucin-Depleted Foci in Rats

Abstract: Processed meat intake is associated with colorectal cancer risk, but no experimental study supports the epidemiologic evidence. To study the effect of meat processing on carcinogenesis promotion, we first did a 14-day study with 16 models of cured meat. Studied factors, in a 2 × 2 × 2 × 2 design, were muscle color (a proxy for heme level), processing temperature, added nitrite, and packaging. Fischer 344 rats were fed these 16 diets, and we evaluated fecal and urinary fat oxidation and cytotoxicity, three biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 56 publications
9
76
1
Order By: Relevance
“…It should be noted that very large amounts of "freeze dried beef", chicken or "black pudding" were included into the experimental diets (600 g/kg). Later, the same research group demonstrated that also processed red meat products promote colon carcinogenesis in a rodent animal model Santarelli et al, 2010). The lack of an enterosalivary recycling of nitrate in rats has however cast doubt on the relevance of the results of nutrition and cancer studies in this animal species.…”
Section: Hemementioning
confidence: 99%
“…It should be noted that very large amounts of "freeze dried beef", chicken or "black pudding" were included into the experimental diets (600 g/kg). Later, the same research group demonstrated that also processed red meat products promote colon carcinogenesis in a rodent animal model Santarelli et al, 2010). The lack of an enterosalivary recycling of nitrate in rats has however cast doubt on the relevance of the results of nutrition and cancer studies in this animal species.…”
Section: Hemementioning
confidence: 99%
“…The perception of conventional red meat is relatively negative due to its high content in fat and saturated fatty acids, cholesterol, sodium and any other substances that may be involved in most prevalent diseases like cardiovascular diseases and diabetes (Micha et al 2010) and cancer (Cross et al 2010;Santarelli et al 2010). As an alternative to red meats, camel meat is considered a good source of high-quality protein with less fat, less cholesterol and a relatively higher amount of polyunsaturated fatty acids .…”
Section: Introductionmentioning
confidence: 99%
“…This path explains meat-induced promotion of tumorigenesis, via selection of the mutated precancer cells in the colon mucosa (Pierre et al, 2004). Several whole foods promote carcinogenesis in rats: hot-dog, cooked ham, blood sausage (not cured), and several workshop-cured meat products (Pierre et al, 2004;Santarelli et al, 2010Santarelli et al, , 2013. The effect of meat on suspected cancer initiators and promoters can be measured in the feces as products of nitrosation and lipoperoxidation (Pierre, Santarelli, Tache, Gueraud, & Corpet, 2008;Pierre, Tache, Petit, Van der Meer, & Corpet, 2003;Santarelli et al, 2013).…”
Section: Cell Culture Studies Animal Experimentsmentioning
confidence: 99%
“…Anaerobic processing and packaging of ham are associated with reduced carcinogenesis in rats (Santarelli et al, 2010). Addition of certain phytochemicals to the meat may have both antimicrobial functions and cancer protective effects (de Oliveira et al, 2010;Shu et al, 2010).…”
Section: It's Not Just Meat On the Platementioning
confidence: 99%